Determinants of college major choice: Identification using an information experiment - Matthew Wiswall; Basit Zafar (Federal Reserve Bank of New York, 2011)
This paper studies the determinants of college major choice using a unique information experiment embedded in a survey. We first ask respondents their self-beliefs - beliefs about their own expected earnings and other major-specific outcomes conditional on various majors, their population beliefs - beliefs about the population distribution of these characteristics, as well as their subjective beliefs that they will graduate with each major. After eliciting these baseline beliefs, we provide students with information on the true population distribution of these characteristics, and observe how this new information causes respondents to update their beliefs. Our experimental design creates unique panel data. We first show that respondents make substantial errors in population beliefs, and logically revise their self-beliefs in response to the information. Subjective beliefs about future major choice are positively and strongly associated with beliefs about self-earnings, ability, and spouse's earnings. However, cross-sectional estimates are severely biased upward because of the positive correlation of tastes with earnings and ability. The experimental variation in beliefs allows us to identify a rich model of college major choice, with which we estimate the relative importance of earnings and earnings uncertainty on the choice of college major versus other factors, such as ability to complete coursework, spouse's characteristics, and tastes for majors. While earnings are a significant determinant of major choice, tastes are the dominant factor in the choice of field of study. We also investigate why males and females choose different college majors.
Keywords: D81; D84; I21; I23; J10; 330; college majors; information; uncertainty; risk; subjective expectations; marriage market returns; gender differences